IMPLEMENTATION OF METACOGNITION QUESTIONS THROUGH THE IMPROVE METHOD TO TRAIN STUDENTS’ MATHEMATIC CRITICAL THINKING ABILITY - Ika Damayanti; Gusniawati; Buhaerah (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
The ability to think critically is one of the very important abilities that students have and improve in learning mathematics. This ability is very necessary to solve daily problems and problems that will come. One of the efforts made to improve critical thinking skills in learning mathematics is by using the IMPROVE method. In the IMPROVE method, the question of metacognition is the main key that must be presented by educators in this method. This question aims to improve the ability to understand, analyze, and self-regulate the application of problem solving, and make connections between initial knowledge and new knowledge. The purpose of critical thinking is to be able to test an opinion or idea, including making considerations or thoughts based on the opinions proposed. Developing one's critical thinking skills can help in making conclusions by considering data and facts that occur in the field. Critical thinking allows students to find the truth amidst the flood of events and information that surrounds them every day (Johnson E, 2002). The calculation of the research result of learning mathematics at SMA Negeri 2 Barru using the IMPROVE method on the Linear Program material obtained the average value is 57.35, the mode value is 54.15, the median is 56.7, the standard deviation is 10.70, the maximum value is 87, the minimum value is 45.